Caring behaviours perceived by elderly residents and their associated factors in nursing homes in Zhengzhou City of China: A qualitative study. (5th December 2020) - Chen, Ruiyun; Dai, Fumin; Yang, Hui; Zhang, Xi; Zhang, Hongmei; Liu, Minhui
Abstract: Caring is an evidence‐supported behaviour or activity which can meet nursing home residents' needs. China has an ever‐increasing number of care‐dependent individuals in nursing homes. It is important to explore the caring behaviours and to understand the factors associated with the caring behaviours perceived by elderly residents in nursing homes. This will contribute to an evidence‐based approach with which to assist healthcare services. This study aims to explore the perceived caring needs, associated behaviours, and their associated factors identified by elderly residents in nursing homes. Fourteen semi‐structured interviews were conducted with elderly residents from five nursing homes in three districts across Zhengzhou City, China. Interviews were transcribed verbatim and analysed using the Colaizzi phenomenological method. Five themes and fourteen sub‐themes were identified. The availability of health services, a livable environment, and social communication were the main caring needs identified. Nursing assistant factors and resident factors were the main influencers. This study provides valuable information on the need to carry out standardised training of nursing assistants and how to adjust the goal of care in nursing home residents. The medical support, psychological counselling, livable environment, recreational and cultural services as well as caring literacy about nursing assistants in the nursing homes, however, need to be further enhanced to meet the residents' diversified caring needs.